Study of Islamic Character Education in the Deli Malay Community, Medan City: Case Study in the Deli Malay Community - Syahputra, Muhammad Ilham; Shittu, Sulayman Adeniran; Ain, Ayesha Qurrat Ul (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This research aims to determine the forms of Islamic character of the Deli Malay community, the formation of Islamic character education in the Deli Malay community, supporting factors for the formation of Islamic character in the Deli Malay community, and the obstacles faced in forming the Islamic character of the Deli Malay community in the Medan Maimun District environment. Methodology: This research uses qualitative research with an ethnographic approach. Using observation, interview and document study data collection techniques. In analyzing the data, researchers used qualitative analysis techniques with data reduction steps, data presentation, and drawing conclusions. Main Findings: Forms of Islamic character such as honesty, responsibility, tolerance and deliberation are strongly reflected in the Deli Malay community in Medan Maimun District. Character formation involves various methods such as teaching, example, habituation, motivation, and enforcing rules. Supporting factors include participation in madrasah or Islamic boarding schools, additional learning in muktabs, and the existence of Malay associations. However, there are also challenges in the process of forming Islamic character, such as the influence of globalization, the lack of Deli Malay culture being maintained, and the lack of figures who can be used as role models. Novelty/Originality of this study: This research explores various methods and strategies used to integrate Islamic values ​​in character education in this community. It is hoped that the results of this research can make a significant contribution to the development of the Islamic character education curriculum in madrasah and provide guidance for educational policy makers to improve the quality of education.